A systematic review of outcomes after stem cell transplantation in acute lymphoblastic leukemia with or without measurable residual disease. Issue 5 (15th April 2020) - Shah, Shweta; Martin, Amber; Turner, Monica; Cong, Ze; Zaman, Faraz; Stein, Anthony
Abstract: This systematic literature review compared clinical outcomes post-stem cell transplantation (SCT) among patients with vs. without the measurable residual disease (MRD) pre-transplant. Relevant literature on adults undergoing transplant with known MRD status pre-transplant was extracted from the MEDLINE, Embase, and CENTRAL databases (through 8 May 2018) and oncology conferences (2014–2018) using keywords for acute lymphoblastic leukemia and MRD. Thirty primary studies reporting SCT outcomes were identified. Hazard ratios (HRs) for overall survival indicated that patients with MRD pre-transplant were more likely to die post-SCT vs. patients with no detectable MRD (HR: 1.51–3.856). In post-SCT relapse studies, 16–100% of patients with MRD vs. 0–50% of patients without MRD relapsed. This review found evidence of markedly worse outcomes post-transplant among patients with vs. without MRD pre-transplant, including shorter median survival (overall, relapse-free, and event-free survival), higher risk of death, more relapse events, and decreased likelihood of remaining in hematologic remission.